(3GdfhGOQ hGdRjGOGJ Ydi eGaj GdeOhfI hZjQgG ef GdCegGJs - (3YHO Gddg Hf YHO GdQMef GdfaRi GdbjQhGfi GdeGdcj , CHh eMeO , GHf CHi RjO , J (B386 (3g`s; (3YHO Gdedc Hf MHjH Hf SdjeGf Hf gGQhf GdSdej GdGdHjQj GdbQWHj, CHh eQhGf,J (B238 (3g` s
(3ChdgG (B:s
(3bGd CHh eMeO YHO Gddg Hf CHj RjO Gdabjg (B: (3GdMeO ddg GdPi HSW fYeJg hGbGe MLJg s
(3BNQgG (B:s
(3jfJgi HGdcdGe ajef Mda dGjTQH NeQkG aTQH fHjPG eScQkG ef cJGH GdfPhQ GdChd s
(3fSNI Ydi Qb ZRGds
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B157s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs